Meningkatkan Kemandirian Perawatan Diri Ibu Postpartum Melalui Transformational Leadership: Literature Review - Steffy Putri Amanda; Luky Dwiantoro (Journal of Health (JoH), 2019)
Background: Self-care for postpartum mothers is very necessary, based on Orem's theory that humans basically have the ability to care for themselves. The way to improve mother's independence is by the influence of a leader (health worker). Transformational leadership is a leadership style that can motivate subordinates to be able to do better, in this case can be applied in improving the independence of postpartum mothers. Objective: Provide an overview of how to improve self-care of postpartum mothers through transformational leadership. Method: The method used in the search process using the PubMeds website, Nursing Journal Bina Husada, Diponegoro Nursing Journal. Search keywords are independence, postpartum mothers, self care. Result: Idealized / Charismatic Influence: the influence of a leader is needed to create an ideal influence, the experience of childbirth supports the ability of postpartum mothers to perform postpartum care. Inspirational Motivation: motivation and inspiration that can provide encouragement, independent family development affects the level of mother's independence. Individualized Consideration: a nurse must be able to respect the patient's background and environment in order to create a harmonious relationship and increase the patient's confidence. Intellectual Stimulation: transformational leadership style that encourages subordinates to solve problems carefully, the higher the level of knowledge the easier it is to receive information. Conclusion: Postpartum mother independence can be improved through transformational leadership